$U$-NUMBERS IN FIELDS OF FORMAL POWER SERIES OVER FINITE FIELDS. Issue 2 (29th April 2020) - KEKEÇ, GÜLCAN
Abstract : In the field $\mathbb{K}$ of formal power series over a finite field $K$, we consider some lacunary power series with algebraic coefficients in a finite extension of $K(x)$ . We show that the values of these series at nonzero algebraic arguments in $\mathbb{K}$ are $U$ -numbers.